Brightbill’s Character Development in The Wild Robot (2024): A Three-Dimensional, Plot, and Self-Determination Analysis - Hana Syaffa Azzahra; Wahyu Budi (Indo Publishing, 2026)
This research explores the character development of a major character in The Wild Robot movie (2024), Brightbill, a Canada goose. Brightbill as a major character is depicted as a weak and dependent figure until finally over time he learns to live like a normal Canada goose and transcend against his own weaknesses. The method used in this research is the qualitative method. Using Lajos’ theory to describe the character of Brightbill’s, and William Kenney’s theoretical framework to explores Brightbill’s character, characterization, and character development through the narrative, also Ryan and Deci’s to reveal the factors of character development in the story. The result of this research is to show the growth and transformation in the characters throughout the storyline that make the characters better than before in the end. Beside this research contains many moral values to the audience, therefore, Brightbill's character development in The Wild Robot movie (2024) reflects a complex and emotional journey from fear and withdrawal to acceptance and courage. This transformation is not only a story of self struggle, but also illustrates how Brightbill’s character development is shaped through choices and conflicts.”